ENVIRONMENTAL SAFETY VITICULTURE IN UKRAINE (EXAMPLE SEBASTOPOL VINEYARDS) - and; and (Municipal economy of cities. Series: «Economy science», 2013)
The paper is focused on factors affecting the quality and environmental safety of wine. The results present processes of migration and accumulation of trace metals in water used for the irrigation, soils of vineyards, vine’s leaves and berries, juice. Potential sources of trace metals in wine products were identified.